227 Fertility-sparing treatment in advanced borderline ovarian tumors. an analysis from the mito14 study database. (4th December 2020) - Falcone, Francesca; Greggi, Stefano; Iaco, Pierandrea De; Ferrandina, Gabriella; Cormio, Gennaro; Donato, Violante DI; Mangili, Giorgia; Raspagliesi, Francesco; Malzoni, Mario; Breda, Enrico
Abstract : Introduction/Background: For advanced borderline ovarian tumors (BOTs), data concerning the efficacy and safety of fertility-sparing surgery (FSS) are very limited. The MITO14 is a multi-institutional retrospective study conducted among MITO Centres with the aim of systematically collecting data from consecutive BOT patients. In the present analysis, data are presented on women with advanced BOT registered into the MITO14 database and conservatively treated between January 1995 and December 2019. Methodology: The objectives were: i) to evaluate the recurrence rate and to determine predictors of recurrence; ii) to assess the impact of a FSS on disease-free survival (DFS) and disease-specific survival (DSS); iii) to evaluate pregnancy and live birth rates following treatment. Only patients undergoing FSS and with histologically proven FIGO2014 stage II – III BOTs at final pathology were included. Cases submitted to bilateral salpingo-oophorectomy with uterine preservation were eligible. The following exclusion criteria were considered: i) age >45 years; ii) presence of second tumor(s) requiring therapy interfering with the treatment of BOT. Results: A total of 101 patients were recruited. The median follow-up time from primary cytoreduction was 124 months (IQR range 80–177.5). Fifty-five patients (54.5%) experienced at least one recurrence (median time to first relapse 21 months, IQR range 9–53), 53 of whom (96.3%) undergoing secondary surgery (further FSS in 34). At univariate analysis, significant predictors of relapse were: size of largest extra-ovarian lesion, peritoneal cancer index, completeness of cytoreduction, type of implants. After multivariable analysis, the size of extra-ovarian lesions and the presence of invasive implants resulted as the only independent predictors of recurrence (Tab. 1). Median DFS and DSS were respectively 96 months (95% CI, 17.5–174.4) and 290.4 months (95% CI, 280.8–299.9) (figure 1). Thirty-one patients attempted to conceive: 23 (74.2%) achieved at least one pregnancy and 20 (64.5%) gave birth to a healthy child. At the end of the observation period, 96 patients (95%) showed no evidence of disease, 2 (2%) were alive with disease, and 3 patients (3%) died from BOT. Conclusions: Despite the recurrence high rate, the survivals and pregnancy outcomes indicate that FSS could be considered in advanced BOTs. Among predictors of recurrence, oophorectomy (vs. cystectomy) has resulted not significant as in early-stage BOTs likely due to the advanced-stage setting. Size of extra-ovarian lesions and presence of invasive implants were the only significant predictors. Completeness of cytoreduction was lacking significance likely because of low number of patients with residual disease. Disclosures: All authors declare no financial support or relationships that may pose conflict of interest.